GERAKAN SEHAT CEGAH HIPERTENSI MELALUI PENYULUHAN, PEMERIKSAAN TEKANAN DARAH, DAN SENAM HIPERTENSI PADA LANSIA DI KELURAHAN KARANGANYAR KOTA TASIKMALAYA - Naila Aprillyani; Dila Ananda Herdiana; Silvia Rizki Nurcahyani; Rina Karlina; Kania Risnawati; Najma Fawaz Bilqisthi; Siti Nafisatul Mutmainah; Hana Sukmawati; Mohamad Tahqiq Abdul Jabbar; Beni Ahmad Yunan; Rois Bustomi; Lany Prasiska Aprianis; Hasya Syah Pradipta; Lutfi Barkah Ramadhan; Dhiya Aqillah Zain; Hasna Siti Nur Rahmah; Laisya Putri Maulida Rahmi; Intan Maulida; Herna Aulia; Fiani Septi Mutmainah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Hypertension is a common health problem often referred to as a "silent killer" because it usually does not show obvious symptoms until complications arise. The Karanganyar Community Health Center (Puskesmas) working area in Kawalu District, Tasikmalaya City, is among the five locations with the highest hypertension rates in the city. The activity aimed to improve participants’ knowledge, awareness, and skills in preventing and controlling hypertension through health education, blood pressure screening, and hypertension exercise. The activity was conducted on August 9, 2026, at Madrasah Al-Muttahid, Karanganyar Village, Kawalu District, Tasikmalaya City, and involved 28 older adults. The activities consisted of preparation, health education, blood pressure screening, hypertension exercise practice, and evaluation through discussion and observation. The results indicated that participants showed better understanding of hypertension-related information and were able to follow the demonstrated hypertension exercise movements. Participants also demonstrated active involvement and enthusiasm throughout the activity. However, changes in blood pressure could not be evaluated optimally because blood pressure measurements were not conducted using a standardized pre- and post-exercise assessment. Therefore, the findings primarily describe participants’ understanding, participation, and ability to perform the exercise after the educational intervention